THE IMPACT OF FINANCIAL POLICIES ON PROMOTING THE DEVELOPMENT OF GREEN INNOVATION - Turgay Nasirli (Agora International Journal of Economical Sciences (AIJES), 2024)
This research investigates the factors influencing the development of green patents and their implications on green innovation. Green financing has the purpose of funding environmental initiatives by directing capital from financial institutions to eco-friendly projects. Through a review of existing literature and empirical analyses, we identify the influence of financial variables and economic policy strategy as key contributors. Preliminary findings suggest that these factors significantly impact the prevalence of green patents, highlighting the importance of policy and financial decisions in fostering environmentally sustainable technological advancements. Our findings reveal a positive correlation between environmental R&D expenditure and green innovation. Moreover, venture capital emerges as a significant driver of green innovation, facilitating the development of environmentally conscious solutions by mitigating financial risks. Additionally, the stringency of environmental policies and the presence of green bonds and carbon taxes demonstrate positive associations with green innovation. Consequently, the main objectives of this article are to examine the impact of financial policies such as R&D, Venture Capital, Debt financing and environmental regulations on the development of green patents and innovation as well as investigate the relationship between green bonds, carbon taxes and green innovation. Ultimately, this research contributes to the ongoing discourse on sustainable development, offering a nuanced understanding of the dynamics driving green innovation.
Keywords: 330